Correlation between quadriceps and hamstrings inter-limb strength asymmetry with change of direction and sprint in U21 elite soccer-players - Coratella, G.; Beato, M.; Schena, F. (Human Movement Science, 2018)
The aim of this study was to investigate the relationship between in quadriceps and hamstrings inter-limb strength asymmetry and change of direction, sprinting and jumping abilities in U21 elite soccer players. Twenty-seven soccer players volunteered for this study. Isokinetic quadriceps and hamstrings peak torque was measured at high and low angular velocities, both in concentric and eccentric modalities. Performance in agility T-test, 20+20m shuttle-test, 10m and 30m sprint, squat jump (SJ) and counter-movement jump (CMJ), were measured. Overall, time on agility T-test and 20+20m shuttle-test was moderately and positively correlated with the quadriceps and hamstrings inter-limb eccentric peak torque asymmetry, both at high and low angular velocities. In addition, time on 10m and 30m sprints was moderately and positively correlated with the hamstrings inter-limb high-velocity concentric peak torque asymmetry. SJ and CMJ showed trivial to small correlations with hamstrings and quadriceps inter-limb peak torque asymmetry. The present results provide further information insight the role of lower-limb muscle strength balance in COD, sprinting and jumping performance.